Species catalogue of Drymaeus (Mesembrinus) Alberts, 1850 (Gastropoda: Bulimulidae) from Brazil and new data on morphology and distribution of Drymaeus (Mesembrinus) interpunctus (Martens, 1887) - Macedo, Maria Isabel Pinto Ferreira; Ovando, Ximena Maria Constanza; D’ávila, Sthefane (PeerJ, 2023)
Background Herein, we attempted to obtain detailed data on the distribution of the species of Drymaeus (Mesembrinus) in Brazil, using biodiversity databases, malacological collections and literature as sources of occurrence records. We provided a catalogue of species, along with distribution maps. We also estimated the suitable distribution of Drymaeus (Mesembrinus) interpunctus using the maximum entropy approach. A detailed description of the anatomy of the soft parts of this species was provided, with new data on the pallial system. Materials and Methods For each species we provided information on the compiled data associated with museum collections and the literature. Distribution maps including geographic boundaries, Brazilian biomes and altitude were made with QGIS software 3.16.10 Hannover. For niche modelling, nineteen bioclimatic variables and a topographic variable were used as predictors. The models were performed with MaxEnt version 3.3.3k. Results Most of the species are represented by scarce material in malacological collections; for some species, these records correspond to type material, indicating that they have not been recollected. Most of the species were represented by shells making anatomical comparison and DNA analysis difficult, limiting our ability to provide new criteria for species delimitation. Our results allowed us to expand the known distribution area for three species, Drymaeus dutaillyi, D. gereti and D. oreades, with new occurrence records in Brazil. The MaxEnt model showed a thin area of high suitability to D. (M.) interpunctus in the Southeastern Brazil, corresponding to the Atlantic Forest. Minimum temperature of the coldest month and mean temperature of coldest quarter were the variables that most influenced the development of the model. Discussion Drymaeus interpunctus was described based on specimens collected in Brazil without mention to the exact localities. Herein the new records from databases allowed to expand the known geographic distribution for this species and to infer its potential distribution. Although the type locality of D. interpunctus is in Brazil, the anatomy of the soft parts of specimens from this country was not previously described. The anatomy of the reproductive system of the specimens analyzed herein mostly corresponds to a previous description for specimens from Paraguay, except for the absence of penial sheath and the relative length of the bursa copulatrix duct. The results of niche modeling showed a thin area of high suitability for D. interpunctus and a vast area of moderate suitability, indicating that this species present a niche breadth that favors its occurrence in a range of different biomes, including less suitable areas. Conclusion The small number of records obtained for most of the species and their restricted ranges associated with habitat destruction may indicate that they are of conservation concern.
Keywords: Land snail; Potential distribution; South America; Peltellinae